MAHMUDXOʻJA BEHBUDIY AS THE FIRST AUTHOR OF DRAMA IN UZBEK LITERATURE - Sitora Suxonberdiyeva (Ethiopian International Journal of Multidisciplinary Research, 2025)
This article examines Mahmudxo‘ja Behbudiy’s pioneering role as the first Uzbek playwright and founder of modern Uzbek drama. It explores how Behbudiy introduced new literary forms and dramatic techniques to Uzbek literature, addressing social issues such as education, enlightenment, and reform. By analyzing his key plays and their historical context, the study highlights Behbudiy’s significant contribution to the cultural revival of Central Asia and the development of Uzbek theater. The article also discusses the lasting influence of his work on subsequent generations of Uzbek writers and dramatists.